NURSING CARE TO TRAUMATIC BRAIN INJURY PATIENTS: AN INTEGRATIVE REVIEW - Carlos da Silva, Roberto; Evelly da Silva Olanda, Débora; Victor Assis Eloy, Allan; Aparecida da Silva de Sousa, Dyanna; Kelly Paes, Gracy; Ellen Costa Vasconcelos, Eduarda; Borim de Oliveira Marques, Cintia; Teles Frazão, Cristiane; Mendes Ribeiro de Oliveira, Carolline (Health and Society, 2023)
Objective: This study aims to identify and evaluate the care provided by the nursing team, to learn more about the role of nurses in TBI, as well as their main care measures for the patient. Method: This is an integrative review of the last 9 years, of the following databases: Scielo, BVS, LILACS and Google Academic. Results: Traumatic Brain Injury better known by the acronym TBI is a pathology resulting from an aggression to the brain. Considered one of the main public health problems worldwide, traumatic brain injury is becoming increasingly more common in the modern world. It is fundamental that the care to the trauma victim be fast and efficient with trained health professionals, emphasizing that the nurse stands out for his peculiar attributes of care and organization of a diminished assistance. Conclusion: Knowledge about trauma kinematics and the physiopathology of TBI facilitates the care and handling of victims, in addition to minimizing the incidence of possible injuries or sequelae, making it essential to develop studies on the subject, so that nursing professionals are trained and perform their activities in an increasingly effective way.